Performance of Used Engine Oil in High Strength Concrete and Behavior of the Structure under Dynamic Loading - Mohamad Rosalan, Mohamad Attirillah (Universiti Teknologi Petronas, 2008)
There is current trend all over the world to investigate waste material as raw material in cement and concrete. This report briefly discusses the preliminary research done and fundamental understanding of the Performance of Used Engine Oil in High Strength Concrete and Structure Behavior under Dynamic Loading. The objective of project is to determine the performance and dynamic behavior of high strength concrete containing used engine oil as additive and to compare the performance of used engine oil with other admixtures. Other admixtures will be included as a comparison for the used engine oil such as superplasticizer, silica fume and rice husk ash. The dynamic load test was carried out as the age of sample reach 28 days. The dynamic load test is subjected to the fatigue failure. For this project the cyclic load test was carried out until 50000 cycles. Thus all samples were analyzed base on the data and result at 50000 cycles. The samples containing rice husk ash, silica fume and superplasticizer were show great dynamic behavior performance compare to the control mix. But for sample containing used engine oil was showed poor dynamic behavior performance since it was failed at 2600 cycles.